2022
DOI: 10.1016/j.hpb.2021.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Total pancreatectomy as an alternative to high-risk pancreatojejunostomy after pancreatoduodenectomy: a propensity score analysis on surgical outcome and quality of life

Abstract: Background: Total pancreatectomy (TP) is mentioned as alternative to pancreatoduodenectomy (PD) with high-risk pancreatojejunostomy (PJ) to avoid severe pancreatic fistula-related complications, but its benefit is controversial and comparative studies are scarce.Methods: Cross-sectional single-center study among patients after PD with high-risk PJ versus patients after single-stage elective TP for any indication (2015-2017), using propensity scores to evaluate surgical outcomes and long-term quality of life (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 54 publications
3
26
0
6
Order By: Relevance
“…Major complications (Clavien-Dindo ≥ IIIb) occurred in 23% within 90 days after surgery, and 90-day mortality was 5.4% in our series of 92 SVPTP patients. TP is known to be associated with high overall perioperative morbidity, with reported major complications of 25.5-34.5% and a mortality of 4-23% [28,[42][43][44][45][46][47]. In this regard, our own results are in agreement with the data in the literature on TP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Major complications (Clavien-Dindo ≥ IIIb) occurred in 23% within 90 days after surgery, and 90-day mortality was 5.4% in our series of 92 SVPTP patients. TP is known to be associated with high overall perioperative morbidity, with reported major complications of 25.5-34.5% and a mortality of 4-23% [28,[42][43][44][45][46][47]. In this regard, our own results are in agreement with the data in the literature on TP.…”
Section: Discussionsupporting
confidence: 90%
“…Patients with vascular resection and reconstruction might be particularly at risk of PPH in case of POPF. Stoop et al demonstrated in a recent study that TP even in the consequence of type III DM (pancreoprivic diabetes mellitus) is [5.4] equivalent to PD in long-term surgical outcome and quality of life [28].…”
Section: Discussionmentioning
confidence: 99%
“…Given an expected occurrence rate of 4 per cent for an outcome this would require a data set of at least 2500 patients. As total pancreatectomy has a high rate of morbidity, it was hoped to be able to produce valid results using a smaller sample 27 . As requests for publication of the detailed model of the ACS SRC have been rejected, automated external validation remains impossible 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite its discriminative value (0.77 [95% confidence interval 0.70–0.83]), the high-risk group had ‘only’ a risk of 6.6% to develop a POPF grade C, suggesting that substantial uncertainty remains [ 5 ]. The major challenge to predict POPF grade C and the associated high mortality could be an argument for a prophylactic total pancreatectomy during index surgery in the presence of very high–risk conditions and carefully selected patients [ 40 , 41 ]. Hereby, simplified pre- and intraoperative predictors can support patient selection and counselling [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%